THE MEDIATING ROLE OF RISK MANAGEMENT PRACTICES IN THE RELATIONSHIP BETWEEN MULTIPLE RISK TYPES AND BANK PERFORMANCE: EVIDENCE FROM COMMERCIAL BANKS IN TASHKENT, UZBEKISTAN - Sardor Kodirov (Modern American Journals, 2026)
This study examines how credit, market, operational, liquidity, and technological risks influence bank performance in commercial banks in Tashkent, Uzbekistan, with risk management practices as a mediator and regulatory compliance and corporate governance as moderators. Primary data from a survey of 100 bank managers revealed that all risk types positively associate with performance, but their effects are primarily mediated by robust risk management practices, increasing explained variance from 40% to 55%. Technological risk emerged as particularly significant. Findings underscore the strategic importance of integrated risk management in emerging markets with limited external hedging options, offering practical recommendations for Uzbek banks and regulators.
Keywords: Bank performance, risk management practices, technological risk, mediation, Uzbekistan.